EFEKTIVITAS GUIDED IMAGERY AND MUSIC (GIM) TERHADAP FATIGUE PADA PASIEN KANKER DI RSUD A. W. SJAHRANIE SAMARINDA - Rufina Hurai (Poltekkes Kemenkes Kalimantan Timur, 2018)
Abstract Cancer is a syndrom of diseases characterized by irregular cell growth. If the spread of uncontrolled cells can cause a variety of complaints and life-threatening. Patients undergoing chemotherapy may experience fatigue complaints (fatigue), weakness, hair loss, nausea, vomiting, dry mouth, anxiety, stress and depression. Relaxation with guided imagery and music is expected to reduce fatigue. This study aims to analyze the effectiveness of guided imagery and music on fatigue cancer patients who underwent chemotherapy at RSUD A.W Sjahranie Samarinda East Kalimantan. The quasi experimental research design, a sample of 95 respondents (71 intervention groups and 24 control groups) was chosen by purposive sampling. Wilcoxon test results have significant changes in fatigue before and after intervention (pvalue 0.00; <0.05). Mann-Whitney test results significantly there is a change of intervention group fatigue with control (pvalue 0.00; <0.05). The probability of event value of guided imagery and music intervention effectively decreased fatigue 0.039 times in the intervention group compared to the control group. Guided imagery and music intervention simultaneously had an effect on fatigue reduction of 73.4%. It is concluded that guided imagery and music is a simple, economical and proven relaxation technique that is effective in reducing fatigue in cancer patients undergoing chemotherapy. Researchers recommend the need for further research to combine guided imagery and music and self-management education on fatigue in cancer patients undergoing chemotherapy and people with similar cancer. Key word: Fatigue, Guided Imagery and Music, Kanker.